2022
DOI: 10.1002/hbm.25887
|View full text |Cite
|
Sign up to set email alerts
|

The orbitofrontal cortex represents advantageous choice in the Iowa gambling task

Abstract: A good‐based model, the central neurobiological model of economic decision‐making, proposes that the orbitofrontal cortex (OFC) represents binary choice outcome, that is, the chosen good. A good is defined by a group of determinants characterizing the conditions in which the commodity is offered, including commodity type, cost, risk, time delay, and ambiguity. Previous studies have found that the OFC represents the binary choice outcome in decision‐making tasks involving commodity type, cost, risk, and delay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 102 publications
3
14
0
Order By: Relevance
“…Specifically, increased age was correlated with reduced activity in the SMA, MFC, SMFC, OFC, and LG, which confirmed our findings in the ANOVA. Consistently, recent studies reported a critical role of the OFC/vmPFC and dorsolateral PFC in modulating young and older adults’ IGT performance ( Rogalsky et al, 2012 ; Tannou et al, 2021 ; Zha et al, 2022a ). Furthermore, brain activations in the MFC and SMFC were positively correlated with CDS, and mediated the relationships between age and task performance in high punishment frequency.…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, increased age was correlated with reduced activity in the SMA, MFC, SMFC, OFC, and LG, which confirmed our findings in the ANOVA. Consistently, recent studies reported a critical role of the OFC/vmPFC and dorsolateral PFC in modulating young and older adults’ IGT performance ( Rogalsky et al, 2012 ; Tannou et al, 2021 ; Zha et al, 2022a ). Furthermore, brain activations in the MFC and SMFC were positively correlated with CDS, and mediated the relationships between age and task performance in high punishment frequency.…”
Section: Discussionsupporting
confidence: 76%
“…We conceptualize that the presence of macroscopic infarcts (as well as AD pathology) impacts these brain networks and degrades specific abilities that may heighten vulnerability to scams. Neuroimaging studies have identified several interacting brain regions within, or highly connected to the frontal lobe, a brain region particularly vulnerable to infarcts (strokes) and β-amyloid pathology in early stages of AD, are likely involved in economic decision-making and socioemotional abilities . Findings from the current study also provides support for a frontal lobe involvement toward decision-making.…”
Section: Discussionsupporting
confidence: 63%
“…The card game test is an adaptation of the Iowa Gambling test and assesses the ability to detect and avoid risky selections and to detect and maintain good selections. Several studies have found this test to be associated with OFC and mPFC (Bolla et al, 2004;Aram et al, 2019;Zha et al, 2022). On the other hand, the maze test assesses the ability to plan, respect limits, and follow the rules.…”
Section: Measures Neuropsychological Battery Of Executive Functions A...mentioning
confidence: 99%